Peptic Ulcer Disease Different Pathogenesis of Duodenal and Gastric Ulcer - Hendra Koncoro; I Dewa Nyoman Wibawa (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Despite decrease frequency of Helicobacter pylori (H. pylori) due to eradication therapy, peptic ulcer disease as a manifestation of this infection is still remain a health burden. Understanding the physiology of gastric acid secretion and its alteration by H. pylori induced inflammation will aid physician in differentiating peptic ulcer disease based on its location. Duodenal ulcer and gastric ulcer disease are two common condition that usually found in peptic ulcer. Recognition of symptoms and its pathogenesis may lead physician to understand the fate of each condition in the future. This article reviews concept of peptic ulcer pathogenesis according to ulcer etiology.